2020
DOI: 10.3389/fmed.2020.585485
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Recurrence of Positive SARS-CoV-2 Results in Patients Recovered From COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19) is spreading throughout the world. Limited data are available for recurrence of positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) results in patients with long duration of COVID-19.Methods: We reported four cases recovered from COVID-19 with recurrence of positive SARS-CoV-2 results during the long-term follow-up.Results: The four patients recovered from COVID-19 showed recurrence of positive SARS-CoV-2 results for more than 120 days with no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…No close contacts or family members were infected. The first time positive Ct value upon hospitalization and second time positive Ct value after discharge, showed no significant difference Zhang et al [77] China Case report 3 1 36,54,50,55 4/- 15 d,25 d,6 d,15 d positive 4 IgG positive 3 IgM positive All presented with no symptoms, and the chest CT scan of three cases was normal Song et al [69] Korea Case report 3 1 73,33,31,18 month 4/- 4 d,9 d,9 d,9 d positive positive In 4 RP patients, the highest levels of IgG and IgM antibodies were reached after about a month of the onset of the initial symptoms. Then, the IgG titers plateaued, and the IgM titers decreased, regardless of RT-PCR results.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…No close contacts or family members were infected. The first time positive Ct value upon hospitalization and second time positive Ct value after discharge, showed no significant difference Zhang et al [77] China Case report 3 1 36,54,50,55 4/- 15 d,25 d,6 d,15 d positive 4 IgG positive 3 IgM positive All presented with no symptoms, and the chest CT scan of three cases was normal Song et al [69] Korea Case report 3 1 73,33,31,18 month 4/- 4 d,9 d,9 d,9 d positive positive In 4 RP patients, the highest levels of IgG and IgM antibodies were reached after about a month of the onset of the initial symptoms. Then, the IgG titers plateaued, and the IgM titers decreased, regardless of RT-PCR results.…”
Section: Resultsmentioning
confidence: 89%
“…There were 34 studies [ 16 , 22 – 24 , 27 , 28 , 32 , 37 , 38 , 40 , 43 , 46 , 47 , 51 , 59 , 60 , 66 , 67 , 69 71 , 75 , 77 , 83 , 85 , 95 , 96 , 98 , 100 , 103 , 106 , 108 , 109 , 117 ] reported that viral RNA could still be detected in patients with SARS-CoV-2 specific IgM and IgG antibodies present, including 234 patients who were IgG positive and 164 who were IgM positive. Fifteen studies reported that both IgG and IgM were positive in RP patients [ 24 , 28 , 32 , 40 , 46 , 47 , 51 , 59 , 60 , 66 , 69 , 70 , 85 , 109 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Ct value of ~25 was identified as the median for virus detection in symptomatic patients, with a consistent proportion of samples (15–25%) falling above Ct 30 [ 25 , 56 ]. Low viral loads are often found in patients with prolonged COVID-19 infection [ [57] , [58] , [59] ], and five of six reported cases of potential re-infection involved samples with Ct values >30 [ 60 ], but whole-genome sequencing is nevertheless recommended to differentiate between relapse and new infections caused by a different SARS-CoV-2 variants [ 60 , 61 ]. The ability to sequence SARS-CoV-2 genomes in low-titer samples is therefore necessary to track infections and correlate different strains with disease communicability, manifestation and severity.…”
Section: Discussionmentioning
confidence: 99%
“…It is not always practicable to validate by sequencing whether specific cases constitute persistence or reinfection, so we have here used the conservative term 'recurrence', except where there are data on infection with a de novo viral sequence. [7][8][9][10] We report a case series of 33 patients with recurrence of COVID-19 symptoms and qRT-PCR positivity and compared them with a control group of 62 patients with a single episode of COVID 19, in a case-control design. Additionally, we were able to compare viral genomes recovered in the first and second episodes for one of these cases.…”
Section: Introductionmentioning
confidence: 99%